Higienização solar de lodo de estação de tratamento de esgoto em estufa agrícola para produção de biossólidos - Alves, Juliane Augusta Dilly (2015)
The sludge generation from Sewage Treatment Plants grows proportionally, when related to population growth, the percentage of treated sewage and the level of efficiency with which they are treated.The final destinations for this byproduct are generally landfills, however, due to the large volume of sludge produced every day, the cost of disposal in landfill is relatively high.Given the potential for agricultural use, this research aimed to study the sludge dewatered sewage treatment plant in drying beds, thus ensuring the reduction of the moisture content and volume of the material and treatment of hygiene in greenhouse agricultural to ensure a low level of pathogenicity.The research was conducted through a test campaign followed by a repetition which occurred from May 28 to August 06 2015.Two sludge piles of the same type were mounted inside the greenhouse , one windrow was put to rest and the other to the revolving once a day on weekdays. Daily the internal temperature was noted and weekly was collected sludge from both piles, for monitoring of physicalchemical and microbiological parameters preset in CONAMA Resolution 375/2006.The results indicated that the sludge from ETE 1, treated by solar hygiene in greenhouses, have better and faster results in reducing pathogens when undergoing breaks. Was found that the mud may be subjected to dehydration and cleaning the bed itself since maintaining the conditions of low humidity or direct solar radiation. Was concluded that the physicochemical and microbiological results of sludge in the study resulted in Class A biosolids, according to research craved.